Space for confrontation: the political caricature of El Rasca-Tripas and the elections,Mexico 1881-1883 - GANTÚS, Fausta (2007)
In this article we propose to reflect on the way in which the political caricature of the Mexican opposition press in the second half of the 19th century was used as a strategy for the construction and dissemination of negative impressions concerning the electoral process. The focus of this work is a case study of the only opposition newspaper during the Government of President Manuel González (1880-1884): the weekly El Rasca-Tripas , and its political cartoons. Based on a comprehensive review of the graphic illustrations published on its pages, we selected for analysis some of the most interesting and representative satirical cartoons. This was done in order to examine the treatment given a number of subjects: suffrage; the role of the political leaders in the context of intentions and definitions of the elector process; and the aspirations of certain protagonists, their inter-relations and internal conflicts and the strategies that were deployed for the achievement of their objectives.